Epistemologi Rasionalisme Rene Descartes Dan Relevansinya Terhadap Pendidikan Islam - Khaeroni, Cahaya (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2014)
This paper discusses the thoughts of Rene Descartes and the relevance towardsIslamic education. The great thesis of Rene Descartes is cogito ergo sum (I think,therefore I exist), has spawned a revolution of thought in philosophy. Descartesemphatically proclaimed that only reason or ratio alone can be the basis that canbe trusted, and not faith or revelation as always restrained in mid-century. Withthe method of doubt, Descartes treading philosophical thought to doubt everythingin order to achieve an ultimate certainty he always longed for. Despite eventuallyhe realized that nothing is true, except uncertainty itself. In the area of education(especially Islamic education), Descartes certainly gave a new foundation for thestudy and communication of doctrine not only as a process doctrine, but giving alarger portion to the role of reason itself.